Stady of the SEMI- Theoretical Relation of the Hydraulic JuMP Evolving in An U-SHaped Channel, With Rough Bed - Ghomri, A.; Debabeche, M.; Riguet, F. (University of Eloued جامعة الوادي, 2009)
This study has for objective to study the theoretical relation of the hydraulic jump by sill, evolving in an U-shaped channel, with a rough bed. Functional relations, in non-dimensional form, relating the jump characteristics, seeming the effect of the bed's roughness, are obtained. A comparative study with the hydraulic jump in U-shaped channel, with smooth bed is proposed.
Articale in Journal of fundamental and Applied Sciences Vol. 01 N. 02
Keywords: hydraulic jump, chanel U , stilling basin, channel bottom rough